Comparison of autogenous tooth bone graft and synthetic bone graft materials used for bone resorption around implants after crestal approach sinus lifting: a retrospective study - Kim, Young-Kyun; Lee, Junho; Yun, Ji-Young; Yun, Pil-Young; Um, In-Woong (Journal of periodontal & implant science, 2014)
This retrospective study compares the amount of bone resorption around implants between an autogenous tooth bone graft (AutoBT) and a synthetic bone graft after a bone-added crestally approached sinus lift with simultaneous implant placements. In all, 37 patients participated in this study. Seventeen patients were grouped as group I and underwent an AutoBT-added sinus lift using the crestal approach. The remaining 20 patients were grouped as group II and underwent synthetic bone grafting. Both groups received the implant placements simultaneously. Of the 37 participating patients, only 22 patients were included in the final results: Eleven patients of group I and 11 patients of group II. Before the surgery, the distance from the alveolar crest to the sinus floor was measured using panoramic radiography. After the surgery, the distance was measured again from the neck of the implant thread to the most superior border of the added graft materials. Then, the amount of sinus lift was calculated by comparing the two panoramic radiographs. After a year, a panoramic radiograph was taken to calculate the resorption of the bone graft material from the radiograph that was taken after the surgery. The significance of the resorption amount between the two types of graft materials was statistically analyzed. The bone height was increased to an average of 4.89 mm in group I and 6.22 mm in group II. The analysis of panoramic radiographs 1 year after the surgery showed an average bone resorption of 0.76 mm and 0.53 mm, respectively. However, the degree of lifting (P=0.460) and the amount of bone-grafted material resorption (P=0.570) showed no statistically significant difference. Based on this limited study, AutoBT can be considered a good alternative bone graft to a synthetic bone graft in a bone-added sinus lift, when extraction is necessary prior to the surgery.